(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The study examined the effect of board characteristics on the corporate reserve of listed service firms in Nigeria. The specific objective was to examine the effect of board gender diversity, board diligence, board independence and board size on the earnings retention rate of listed service firms in Nigeria. Ex-post facto research design was adopted in the study. The population comprised all the 21 listed service firms in Nigeria. Purposive sampling was deployed in selecting the sample size of 16 firms. Secondary data were collected from the firms’ annual reports over an eleven year period from 2014-2024. Descriptive analysis was carried out on the data after which tests of cross-sectional and heteroskedasticity were conducted. Panel estimated generalised least square regression was used to test the hypotheses. The findings revealed that: board gender diversity has a positive and significant effect on earnings retention rate among listed service firms in Nigeria (β = 35.5009; p = 0.0014); board diligence has a positive and significant effect on earnings retention rate among listed service firms in Nigeria (β = 1.4354; p = 0.0162); board independence has a negative but non-significant effect on earnings retention rate among listed service firms in Nigeria (β = –0.0264; p = 0.9966); board size has a negative and insignificant effect on earnings retention rate among listed service firms in Nigeria (β = –0.1175; p = 0.8411). In conclusion, while traits such as gender inclusiveness and diligence appear to strengthen internal capital accumulation, the non-significant outcomes associated with board size and independence suggest that formal structures alone are not sufficient. The study recommends that listed service firms in Nigeria need to institutionalize gender-inclusive board policies by setting internal targets or quotas for female representation. In addition, companies should focus on recruiting competent and experienced female professionals, not just for compliance, but to strategically improve long-term financial sustainability through prudent profit retention.